QUESTION BANKING FOR ENGLISH COMMUNICATION SKILLS COURSES: A GUIDE - El Malak, Mirna Abd (European Scientific Journal, ESJ, 2013)
With the advent in computers and the Internet, item banking emerged as an effective approach to testing. One of the many responsibilities currently burdening educators is regularly building tests. A question bank can help reduce the workload of constantly developing tests. A carefully constructed question bank renders test building efficient and the evaluation of learning more structured and criteria based. The significance of item banking stems from the increased inclination towards standardization in educational institutions. Question banking is a step towards developing standards for testing, getting reliable data and statistics to evaluate the educational process, and making the necessary educational decisions. For this purpose, it is essential that educators be conscious of the various options available before launching an item bank so that their choice be sound and based on the advantages, the disadvantages, and the implementation of each option. This study presents three main possibilities to launch an item bank: locally developing a software program and constructing items accordingly, leasing or buying item bank software and locally constructing items to supply it with, or buying a readily made item bank and the accompanying software. Clear guidelines and illustrations are provided to help educators construct well-built question banks.